2018
DOI: 10.1111/jir.12472
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of self‐injury, aggression and property destruction in children and adults with tuberous sclerosis complex

Abstract: These findings suggest that self-injurious behaviours in individuals with TSC, together with aggressive and destructive behaviours, are highly persistent and would benefit from targeted intervention. Poor adaptive skills, overactivity/impulsivity and painful health conditions may differentiate those at most risk for persistent self-injury or aggression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
1
16
1
Order By: Relevance
“…Symons et al (2003) reported 84% persistence of self-injurious behavior 1 month after baseline measurement in individuals with FXS. The persistence rate in FXS is also broadly consistent with other populations including heterogeneous ID (71% over 7 years; Emerson et al 2001), tuberous sclerosis complex (85% over 3 years; Wilde et al 2018), and ASD (78% over 3 years; Richards et al 2016).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Symons et al (2003) reported 84% persistence of self-injurious behavior 1 month after baseline measurement in individuals with FXS. The persistence rate in FXS is also broadly consistent with other populations including heterogeneous ID (71% over 7 years; Emerson et al 2001), tuberous sclerosis complex (85% over 3 years; Wilde et al 2018), and ASD (78% over 3 years; Richards et al 2016).…”
Section: Discussionsupporting
confidence: 70%
“…Persistence of aggressive behavior has been reported in children with ID over a 2-year period (69%; Davies and Oliver 2016). Three-year persistence of self-injurious and aggressive behavior has been investigated in specific neurodevelopmental disorders with 84% persistence of self-injury and 67% persistence of aggressive behavior reported in individuals with tuberous sclerosis complex (Wilde et al 2018), and 78% persistence of self-injury in individuals with autism spectrum disorder (ASD; Richards et al 2016). Taken together, this research suggests that the prevalence of self-injurious and aggressive behavior increases with age into adulthood and is highly persistent both in individuals with ID of heterogeneous aetiology and in those with neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that in children and adolescents, overactivity and impulsivity correlates strongly with the presence or absence of ID (de Vries, Hunt, & Bolton, 2007), and there is some indication that overactivity may decrease with age (see Table 2). More nuanced studies of overactivity and impulsivity are warranted to identify priorities for intervention for these problematic behaviours in TSC, particularly given robust associations between impulsivity and self-injury and aggression in TSC (Eden et al, 2014; Wilde et al, 2017; Wilde et al, 2018), suggesting that impulsivity may be a risk marker for these adverse behavioural outcomes.…”
Section: The Behavioural Levelmentioning
confidence: 99%
“…Clinically, we observed that SIB rarely resolves with traditional intervention. In one study, SIB persisted in 84.6% of patients . In our center, we gathered behavioral and medical data for over a year on a patient with TSC‐associated SIB and aggression noting a decrease in SIB primarily with the mTOR inhibitor everolimus .…”
Section: Introductionmentioning
confidence: 99%